PENGARUH PENAMBAHAN SERUM SAPI PADA MEDIA KULTUR TERHADAP KOMPETENSI MEIOSIS OOSITANJING DARI BERBAGAI STADIUM ESTRUS SECARA IN VITRO - Yuda Heru Fibrianto; Claude Mona Airin; Amrullah Anindito; Nuraini Rachmawati (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2011)
Reproduction technology achievement on caninew as fastd eveloped, with born of cloning and transgenic dog, unforfunately that's technology still used oocyte matured in vivo because canine oocyte matwation in vitroin this animaln ot developedy et and mafurationr ates till low. The present study was to investigated the effects of cow serum supplementation on meiotic resumption of canine oocytes from various estms stage. Ovary obtained from bitchesa tan-, pro-and di-estrus stage after ovariohysterectomizeadt clinic veterinarypracticeO. varyw ereplaced in 0.9o/op hysiologycal saline added 1% pennicilline-streptomycinw ith temperature 37'C and then broughtt o laboratoryO. vary washeds everatl imesu sedP BSa ndo ocytesw ere obtained by slicing ovariant issueintissueculturemedium(TCM)-l99 supplemented with 25mMHepes, 1%pennicillin-streptomycin. Selected cummulus oocyte complexes (COCs) were matured in TCM-199 as control and TCM-199 + 10% cow serum as treatment, on incubator with 38C, 5% CO2, and 5% O2. After 72 h incubation and Hoechst 33342 staining, the result shows that cow serum supplement have higher meiotic resumption significantly (P<0.05) in MI achievement han in control and oocyte from proestrusi rave higher meiotic competent(46.5%) comparing oocyte from anestrus(29,4%)s ignificantly(P<0.05) but not significantly(P>0.05) with diestrus stages(34.8%).Keywords: meiosis, oocyte, ovarium, cows serum